Semiotik Roland Barthes dalam Film Animasi Entong Sebagai Implikasi Penerapan Bahan Ajar Sastra di Sekolah Dasar - Nurul Vidiyah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
The problem in this research is the lack of alternative literature teaching materials used by teachers in the learning process. This study aims to analyze the semiotics of Roland Barthes in the animated film Entong which will be used as an alternative material for teaching literature in elementary schools. The research method applied in this research is content analysis method. Data collection techniques were carried out by observation and documentation. The results of the observation show that there are semiotic codes of Roland Barthes in the episodes of the animated film Entong. This happens because, data retrieval is taken from the YouTube application. The semiotic codes contained in the animated film Entong are hermeneutic codes that function to see the problems of a narrative and create a solution or an answer, semiotic codes function to a connecting relation code which is the connotation of a person, place, object whose sign is a character, code symbolic functions as symbols, preauretic codes function to see the basic narrative actions in various sequences that may be indicated, and cultural codes function to see the cultural side of a story. Based on Roland Barthes' semiotics contained in the animated film Entong, it can be used as an alternative to teaching literature in elementary schools so that students can apply it in their daily lives.